2015
DOI: 10.1111/add.12863
|View full text |Cite
|
Sign up to set email alerts
|

Mortality among individuals accessing pharmacological treatment for opioid dependence in California, 2006–10

Abstract: Aims To estimate mortality rates among treated opioid-dependent individuals by cause and in relation to the general population, and to estimate the instantaneous effects of opioid detoxification and maintenance treatment (MMT) on the hazard of all-cause and cause-specific mortality. Design Population-based treatment cohort study. Setting Linked mortality data on all individuals first enrolled in publicly-funded pharmacological treatment for opioid dependence in California, USA from 2006 to 2010. Particip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
104
1
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 105 publications
(114 citation statements)
references
References 33 publications
(60 reference statements)
6
104
1
3
Order By: Relevance
“…OUD is a chronic, recurrent illness characterized by cyclical episodes of treatment and relapse (6165) and we interpret these cumulative differences between OAT and detoxification as indicative of the stabilizing effects of OAT, akin to previous results showing that OAT access among HIV positive individuals with OUD increased medication adherence and independently reduced all-cause mortality. (66, 67) Whereas the clinical importance of treatment for OUD in reducing opioid-related mortality, (1, 2) controlling infectious disease, (68) and improving patients’ lives (47) has been previously shown, we have demonstrated a compelling case for the importance of evidence-based treatment in reducing the economic burden imposed on society by OUD.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…OUD is a chronic, recurrent illness characterized by cyclical episodes of treatment and relapse (6165) and we interpret these cumulative differences between OAT and detoxification as indicative of the stabilizing effects of OAT, akin to previous results showing that OAT access among HIV positive individuals with OUD increased medication adherence and independently reduced all-cause mortality. (66, 67) Whereas the clinical importance of treatment for OUD in reducing opioid-related mortality, (1, 2) controlling infectious disease, (68) and improving patients’ lives (47) has been previously shown, we have demonstrated a compelling case for the importance of evidence-based treatment in reducing the economic burden imposed on society by OUD.…”
Section: Discussionmentioning
confidence: 56%
“…Specifically, as previously shown within this study’s cohort, the standardized mortality ratio in the two-week period following treatment discontinuation was 31.5 (95%CI: 26.2, 37.5) compared to 1.8 (1.6, 2.1) during treatment and 6.1 (5.7, 6.5) during all out-of-treatment periods. (1) Our observation that individuals with OUD had relatively little exposure to maintenance-oriented treatment over the duration of follow-up, despite its proven effectiveness, further highlights the need to improve treatment-engagement strategies.…”
Section: Discussionmentioning
confidence: 96%
“…Noteworthy is that a similar mortality rate was recently reported in a 4.5-year (mean) follow-up study of patients who had been randomized in an opioid treatment programme to receive open-label methadone or buprenorphine/naloxone [26]. Furthermore, Evans et al [39] found a 3.2% mortality rate in 32,322 individuals in pharmacological treatment over a 2.6-year (mean) treatment period; mortality was highest when individuals were out of treatment and during detoxification, particularly in the 2-weeks post-treatment entry. Degenhardt et al [40] estimated the mortality reduction in opioid maintenance therapy to be 29%.…”
Section: Discussionmentioning
confidence: 71%
“…A more detailed examination with more frequent HRQoL measurements and complete information on medication receipt may further clarify the long-term effects of OAT on HRQoL, in the interest of producing unbiased assessments of competing treatment modalities. It should be clear, however, that the QALY gains derived from the reduction in the risk of mortality attributable to OAT (Degenhardt et al, 2011; Evans et al, 2015; Nosyk, Min, et al, 2015), drive results in economic modeling efforts and underline the importance of this life-saving treatment.…”
Section: Discussionmentioning
confidence: 99%